Is Advance Maternal Age an Indication for Fetal Echocardiogram? [18P]. (May 2017) - Patel, Krunal; Parikh, Bijal; Guirguis, George; Williams, Shauna; Apuzzio, Joseph
Abstract : INTRODUCTION: Pregnancies in women of advanced maternal age (AMA) are at increased risk for aneuploidy and therefore could be at increased risk for congenital heart disease (CHD). Our objective was to assess whether AMA without another risk factor for CHD is associated with abnormal fetal echocardiogram. METHODS: This is a retrospective cohort study of all patients who were referred for specialized sonogram and fetal echocardiogram January 1, 2015 through December 31, 2015 at a single academic institution. Data was collected on demographics, indications for specialized sonogram and fetal echocardiogram, aneuploidy screening, amniocentesis results and obstetric outcomes. Patients were grouped by age (< 35 or > 35 at delivery) and rate of abnormal fetal echocardiograms were compared by Fisher's exact test. RESULTS: 483 patients underwent specialized sonogram, 189 (39%) were AMA patients. Fetal echocardiogram was performed in 87 (46%) patients in the AMA group versus 134 (45.4%) patients in the non-AMA group. Abnormal fetal echocardiograms were found in 2 (2.2%) of the AMA group compared to 8 (6%) of the non-AMA group (p=0.32). Of the 65 AMA patients who did not have another indication for fetal echocardiogram, 2 (3%) had abnormal results (mild cardiomyopathy, VSD) whereas there were no abnormal echocardiograms in AMA patients with another indication (0/22). One of the two patients had an abnormal quad screen for increased risk for trisomy 21. CONCLUSION: In this cohort, AMA without another indication for fetal echocardiogram had a 3% rate of abnormal fetal echocardiogram. This suggests that a fetal echocardiogram should be considered in patients who are AMA.